Bioinspired Microhinged Actuators for Active Mechanism‐Based Metamaterials - Zi‐Yi Cao; Huayang Sai; Weiwei Wang; Kai‐Cheng Yang; Linlin Wang; Pengyu Lv; Huiling Duan; Tian‐Yun Huang (Advanced Science)
Abstract Mechanism‐based metamaterials, comprising rigid elements interconnected by flexible hinges, possess the potential to develop intelligent micromachines with programmable motility and morphology. However, the absence of efficient microactuators has constrained the ability to achieve multimodal locomotion and active shape‐morphing behaviors at the micro and nanoscale. In this study, inspiration from the flight mechanisms of tiny insects is drawn to develop a biomimetic microhinged actuator by integrating compliant mechanisms with soft hydrogel muscle. A Pseudo‐Rigid‐Body mechanical model is introduced to analyze structural deformation, demonstrating that this hydrogel‐based microactuator can undergo significant folding while maintaining high structural stiffness. Furthermore, multiple microhinged actuators are combined to facilitate folding in multiple degrees of freedom and arbitrary directions. Fabricated by a multi‐step four‐dimensional (4D) direct laser writing technique, the microhinged actuators are integrated into 2D and 3D metamaterials enabling programable shape morphing. Additionally, micro‐kirigami with photonic structures is demonstrated to show the pattern transforming actuated by the microhinges. This bioinspired design approach opens new avenues for the development of active mechanism‐based metamaterials capable of intricate shape‐morphing behaviors.